Kjell Goldmann, Sten Berglund, Gunnar Sjostedt, Democracy and Foreign Policy. Case of Sweden, Swedish Studies in international relations, 17, Aldershot: 1986, 206 s., $ 34,50. - Heurlin, Bertel (Politica, 1987)
-